N-3 fatty acid EPA supplementation in cancer patients receiving abdominal radiotherapy - A randomised controlled trial. (June 2021) - Patursson, Poula; Møller, Grith; Muhic, Aida; Andersen, Jens Rikardt
Summary: Background & aims: Malnutrition occurs frequently in patients with cancer during and after radiotherapy to the gastrointestinal (GI) and pelvic area and can lead to negative outcomes. N-3 fatty acids from fish, especially eicosapentaenoic acid (EPA) may possess anticachectic properties. The aim of this study was to investigate the effect of two nutritional interventions; dietary counselling and a daily oral nutritional supplement (ONS) containing 33.8 g of protein and 2.2 g EPA and 1.1 g docosahexaenoic acid (DHA) or standard care, including dietary counselling and protein supplementation when needed. Methods: Outpatients commencing radiotherapy to the GI area were randomized to receive dietary counselling and daily supplementation over a 5-7-week period or standard care. Outcome parameters were measured at baseline (onset of radiotherapy), week 5, and 12 weeks after commencing radiotherapy, with one additional measurement of body weight at week 2. Quality of life (QoL) was measured using the EORTC QLQ-C30 questionnaire. Radiotherapy-related side effects were assessed using a questionnaire developed specifically for this study. Data from a historical control group collected in a previous observational study were included in this study to compare incidence of weight loss. Results: In total, 30 patients were recruited to this study and 26 patients were enrolled and randomised. The rate of withdrawals was 7.7% at week 2, 15.4% at week 5, and 19.2% at week 12. In total, 22 patients completed the intervention. All the patients in the ONS-group and 85% in the control group experienced weight-loss. Using the intention to treat principle, there were no significant differences between groups in any of the outcomes. All patients experienced side effects. Five out of 11 patients consumed more than 75% of prescribed dose of the fish oil enriched oral nutritional supplement. Post hoc analysis showed that at week 2 the weight changed in high-compliant patients was +1.7% (1.0–2.6) compared with −0.7% (−2.8 to −0.1) in low compliant patients (p < 0, 01). The results indicated a dose–response relationship, as correlation analysis recovered a significant positive correlation between weight change and compliance to the fish oil enriched nutritional supplement at both week 2 and 5 (p < 0.05 and p < 0.01, respectively), but not at week 12, indicating a dose–response relationship during radiotherapy but not after. The proportion of patients experiencing weight loss throughout the study period was higher in this study (84.2%) than in the historical control group (73%) (p<0.05%). Conclusion: This study showed no effect from dietary counselling and intended protein/fish-oil supplementation on weight loss, quality of life, and nutritional intake, micronutrient status in plasma or radiotherapy-related side effects compared to the control group. However, the compliance to the fish oil enriched oral nutritional supplement was low. Post hoc analysis of dose–response relations indicate a positive correlation between the compliance and the ability to reduce weight loss in cancer patients during radiotherapy treatment. Trial registration clinicaltrials.gov identifier: NCT04687124.